2017
DOI: 10.3390/ijerph14010038
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Quality of Life in High-Dose Benzodiazepine Misusers

Abstract: Benzodiazepines (BZDs) are among the most widely prescribed drugs in developed countries, but they have a high potential for tolerance, dependence and misuse. High-dose BZD misuse represents an emerging addiction phenomenon, but data on quality of life (QoL) in high-dose BZD misusers are scant. This study aimed to explore QoL in high-dose BZD misuse. We recruited 267 high-dose BZD misusers, compared the QoL scores in those who took BZD only to poly-drug misusers, and explored the role of demographic and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 44 publications
(78 reference statements)
5
32
0
2
Order By: Relevance
“…We prospectively recruited 167 consecutive patients aged >18 years, who were seen from June 2014 to June 2016 at the Department of Medicine, Addiction Medicine Unit, Verona University Hospital, Italy for detoxification from high‐dose BZD dependence. High‐dose BZD dependence was defined as BZD dependence according to DSM‐IV‐TR criteria with abuse lasting >6 months, daily BZD intake exceeding at least five times the maximum daily recommended dose (ie, >50 mg diazepam/day), and/or an otherwise problematic use, such as mixing BZDs, escalating dosage, using BZDs for recreational purposes, or obtaining BZDs illegally . The dosage of BZD was based on self‐report and standardized as daily diazepam dose equivalent (DDDE, mg) according to previous studies .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We prospectively recruited 167 consecutive patients aged >18 years, who were seen from June 2014 to June 2016 at the Department of Medicine, Addiction Medicine Unit, Verona University Hospital, Italy for detoxification from high‐dose BZD dependence. High‐dose BZD dependence was defined as BZD dependence according to DSM‐IV‐TR criteria with abuse lasting >6 months, daily BZD intake exceeding at least five times the maximum daily recommended dose (ie, >50 mg diazepam/day), and/or an otherwise problematic use, such as mixing BZDs, escalating dosage, using BZDs for recreational purposes, or obtaining BZDs illegally . The dosage of BZD was based on self‐report and standardized as daily diazepam dose equivalent (DDDE, mg) according to previous studies .…”
Section: Methodsmentioning
confidence: 99%
“…High‐dose BZD dependence was defined as BZD dependence according to DSM‐IV‐TR criteria with abuse lasting >6 months, daily BZD intake exceeding at least five times the maximum daily recommended dose (ie, >50 mg diazepam/day), and/or an otherwise problematic use, such as mixing BZDs, escalating dosage, using BZDs for recreational purposes, or obtaining BZDs illegally . The dosage of BZD was based on self‐report and standardized as daily diazepam dose equivalent (DDDE, mg) according to previous studies . Zolpidem, which is an imidazopyridine chemically distinct from BZDs, has been included in the present study, since it binds to the alpha‐1 subtype of BZD receptor and its effect is similar to that of BZDs …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated prevalence of higher-thanrecommended dose of anxiolytics and hypnotics was reported to be 0.14 and 0.06%, respectively, in Europe [7], and that of high-dose BZD use to be 0.16% in Switzerland [8]. We have previously found that high-dose BZD use is associated with worse quality of life (QoL) [9,10] and multifocal cognitive dysfunction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since that time evidence of broad-ranging harms resulting from long-term BDZ use has continued to grow, including cognitive deficits [8][9][10], reductions in quality of life [11][12][13], depression [14][15][16], risk of suicide [17], risk for road accidents [18,19], and specific to older adults-the risk of falls [20][21][22], developing dementia [23][24][25], and of mortality [26][27][28]. Short-term, paradoxical effects such as increased anxiety, agitation, disinhibition, and aggression have also been observed [29,30].…”
Section: Costs Of Benzodiazepine Usementioning
confidence: 99%